Effect of intercropping winter-season forage crops on their yield and nodulation - BARIK, A K; TIWARI, D P; TRIPATHI, R S (The Indian Journal of Agricultural Sciences, 2013)
In an experiment on intercropping of fodder crops, berseem [Trifolium alexandrinum (L.) Juslen.] plants in sole and intercropping were taller compared with lucerne (Medicago saliva L.). Among the different cropping systems berseem sole crop gave the highest yield of green and dry forage and economic return. A combination of oat (Avena sativa L.) either with berseem or lucerne in 2 : 2 or 4 : 4 row arrangements respectively gave more green-fodder yield than oat alone. Berseem in sole and intercropping systems produced morenoduleslplant than lucerne. The nodule number started decreasing after second cut (80 days after sowing) both in berseem and lucerne. Hence under medium black-soil conditions berseem as sole and in intercropping gave maximum forage yield and economic return.